Medieval France at War A Military History of the French Monarchy, 885-1305. - France, John (War and Conflict in Premodern Societies Ser., 2022)
An overarching, comprehensive analysis of the French military in the medieval period, focusing on the armies of the French monarchy and the lands close around them, and extending from the Low Countries to Provence.